The Implementation of Tax Administration Digitalization Policy on Tax Compliance in Manufacturing Industry Companies - Roida Roida; Rini Werdiningsih; Emiliana Sri Pudjiarti (Dynamics Social : International Journal of Social Sciences and Communication, 2025)
This study aims to analyze the impact of the implementation of digitalization policy in tax administration through e-Invoice, e-SKP, and e-Bupot systems on tax compliance in manufacturing industry companies, as well as to identify determinants of its effectiveness in enhancing compliance behavior in the era of digital transformation. A descriptive narrative literature review approach was employed, drawing on 52 articles published between 2014 and 2024 from international academic databases such as Google Scholar, ProQuest, and JSTOR. Thematic analysis was conducted to identify recurring patterns and theoretical connections related to digital tax administration and compliance in the manufacturing sector. The findings indicate that digitalization of tax administration has a significant positive impact on compliance, with compliance rates increasing by 42% and non-compliance decreasing from 28% to 12%. Five main pathways were identified: efficiency pathway, transparency pathway, integration pathway, technology acceptance pathway, and trust pathway. These pathways highlight how digital platforms streamline processes, strengthen accountability, facilitate data integration, improve user adoption, and enhance trust between taxpayers and authorities. Furthermore, digital literacy and infrastructure readiness emerged as critical moderators. Companies with high levels of digital literacy experienced a 58% improvement in compliance, whereas those with limited capabilities showed only a 23% increase. Theoretically, the study contributes to the development of a Digital Tax Compliance Model that integrates the Technology Acceptance Model with Tax Compliance Theory, offering a comprehensive framework to explain the complex interactions between technological, organizational, and environmental factors in the success of digital transformation. Practically, the results provide valuable insights for policymakers and tax authorities in designing responsive strategies that strengthen compliance in the manufacturing industry through sustainable digitalization initiatives.